Barang Bukti Dalam Hukum Pembuktian Di Indonesia - Fitri Darizta; Selin Sufitri; Herlina Firdaus; M. Fathony; Desti Indah Sari (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2023)
Proof cannot produce absolute truth, because human knowledge is always relative, dependent on experience, perception, and thinking that may not necessarily be correct. This study uses a normative legal method. In criminal procedure law, evidence is regulated in Article 184 of the Criminal Procedure Code (KUHAP). However, in judicial practice, evidence can change function to become admissible evidence. Although the KUHAP does not explain in detail the meaning of evidence, its position in the process of proof is very important and inseparable from other means of evidence. In some cases, the provisions of Article 184 of the Criminal Procedure Code are considered irrelevant and need to be reviewed and adapted to the times, including the recognition of evidence as a valid means of proof. For judges, prosecutors, investigators, and lawyers, a shared understanding of the importance of the principle of proof, especially in the use of evidence in the form of electronic information or documents in corruption cases, is essential to accurately assess the strength of the evidence